Estimation of Total Suspended Solids in Pung River using Global Precipitation Measurement Data - อ่วงอารีย์ ประวิทย์; พรหมสาขาฯ ชฎาพร; วงค์สีดา ทิติยา; บัวทองจันทร์ ณัฐพัชร์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2018)
The object of this research was investigated the possibility of using Global Precipitation Measurement Data (GPM) for estimating total suspended solids (TSS) in Pung River. The longitudinal change of TSS and the correlations between GPM data and TSS were examined. Moreover, the estimating models of TSS, which use GPM data as input data were developed, by using a Group Method of Data Handling (GMDH). The results indicated that the TSS levels in Pung River hange along the length of the channel, the upstream location had TSS value lower than the end of the river. Intermediate level of relationship between 3-days, 7-days, and 14-days of GPM precipitation and TSS values were disclosed. The TSS models using GPM data as input data had moderate effi ciency; the estimated values and the actual values varied in the same way. The validated models had the coefficient of determination of 0.41 - 0.89.